La voix féminine dans les motets français à deux et trois voix du XIIIe siècle - Rachel Méegens (Transposition)
French polyphonic secular motets are based on polytextuality: several texts are simultaneously set out by several voices. Women’s motets let female voices speak, possibly in interaction with male voices: polytextuality is consequently related to gender problems.As an outcome to Sylvia Huot’s and Mark Everist’s works, we question a corpus of women’s French motets through linguistic, anthropological and theatrical notions. How does the text’s subjectivity work in such a context ? How may it be invested in by performer’s voices ? Emile Benveniste’s theory defines subjectivity as a “speaker’s capacity to come up as a subject”. Subjectivity seems a way of questioning notions of enunciation and focalization related to this type of fictional discourse. This analysis, which takes into account intertextuality, allows to establish a typology of women’s locution in the motet which focuses the light on medieval conceptions of the character’s subjectivity and theatricality. According to these conceptions, one may think about women’s motets medieval and present-day performances.